Weak response of greenhouse gas emissions to whole lake N enrichment. (6th November 2017) - Klaus, Marcus; Bergström, Ann‐Kristin; Jonsson, Anders; Deininger, Anne; Geibrink, Erik; Karlsson, Jan
Abstract: Global warming and land use scenarios suggest increased 21 st century nitrogen (N) inputs to aquatic systems. Nitrogen affects in‐lake processing and, potentially, atmospheric exchange of greenhouse gases, probably being most relevant in unproductive systems. Here, we test for the first time the effect of a whole‐lake experimental increase (threefold) in external nitrate loads on the atmospheric exchange of carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O) from N‐limited unproductive boreal lakes. Nitrate enrichment effects were assessed within a paired Before/After‐Control/Impact framework based on 2‐hourly to biweekly surface‐water sampling of dissolved gas concentrations, and monthly whole‐lake inventory surveys, carried out over 4 yrs in six lakes. Nitrate enrichment did not affect gas exchange during summer stratification and whole‐lake gas inventories during summer and winter stratification. This finding specifically emphasizes the modest role of internal carbon fixation for the CO2 dynamics of unproductive boreal lakes. A global synthesis of 52 published studies revealed a wide range of nutrient fertilization effects, both in systems similar to our experimental lakes, and other more productive systems. Effects depended mainly on the spatiotemporal scale of the study and became more pronounced when N enrichment was combined with phosphorous. Conclusively, although short‐term and habitat‐specific effects can occur, changes in N supply have only weak whole‐ecosystem effects on greenhouse gas emissions from unproductive boreal lakes.